Pengembangan Sistem Helpdesk Berbasis Web Menggunakan Metode Rapid Application Development - Setiawan, Andre Nur; Ferdianata, Hendra Ferdi; Sarumaha, Honorisman; Haryono, Wasis (Journal of Informatics, Electrical and Electronics Engineering, 2025)
Previously, the process of providing information technology device service was still carried out manually, including customer data recording, device documentation, service status updates, and information delivery to customers. This condition potentially caused various problems, such as inaccurate data recording, delays in communication among related parties, and limited managerial capability in monitoring overall service performance. This study aims to design and develop a web-based helpdesk and ticketing system capable of managing the service workflow in a structured, fast, and centralized manner. The system development method employed is Rapid Application Development (RAD), which enables an iterative development process with direct user involvement during the design and prototype evaluation stages. The developed system supports service request submission, customer and device data recording, real-time service status updates, and the provision of operational reports accessible to management. The testing results indicate that the implementation of the web-based helpdesk system improves service data recording efficiency by approximately 60%, increases service data accuracy by up to 80%, and reduces communication delays between customers and service providers. In addition, the provided dashboard feature facilitates management in monitoring technician performance, service status, and operational reports in real time. Therefore, the proposed web-based helpdesk and ticketing system is considered capable of enhancing operational efficiency, service transparency, and overall service quality.